2011
DOI: 10.2215/cjn.07540810
|View full text |Cite
|
Sign up to set email alerts
|

Induction Immunosuppressive Therapy in the Elderly Kidney Transplant Recipient in the United States

Abstract: SummaryBackground and objectives The choice of induction agent in the elderly kidney transplant recipient is unclear. Results In high-risk recipients with high-risk donors there was a higher risk of rejection and functional graft loss with IL2RA versus rATG. Among low-risk recipients with low-risk donors there was no difference in outcomes between IL2RA and rATG. In the two groups in which donor or recipient was high risk, there was a higher risk of rejection but not functional graft loss with IL2RA. Among low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 25 publications
6
59
0
4
Order By: Relevance
“…A study by Gill and associates comparing rATG, alemtuzumab, and interleukin-2 receptor antagonists in kidney recipients aged 60 years and older suggests that rATG may be preferable for both low-and high-immunologic-risk recipients (PRA > 20%, prior transplant or black race) who receive high-risk donor kidneys (ECD, DCD, or cold ischemic time > 24 h). 16 In lower risk donor kidneys, patient and graft survival did not differ. In our relatively large retrospective study, we did not find any significant difference in short-term death-censored graft survival, graft function, rejection or safety (infections and rATG tolerability) between elderly and nonelderly kidney recipients who received rATG induction followed by tripleagent, calcineurin inhibitor-based maintenance regimens.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A study by Gill and associates comparing rATG, alemtuzumab, and interleukin-2 receptor antagonists in kidney recipients aged 60 years and older suggests that rATG may be preferable for both low-and high-immunologic-risk recipients (PRA > 20%, prior transplant or black race) who receive high-risk donor kidneys (ECD, DCD, or cold ischemic time > 24 h). 16 In lower risk donor kidneys, patient and graft survival did not differ. In our relatively large retrospective study, we did not find any significant difference in short-term death-censored graft survival, graft function, rejection or safety (infections and rATG tolerability) between elderly and nonelderly kidney recipients who received rATG induction followed by tripleagent, calcineurin inhibitor-based maintenance regimens.…”
Section: Discussionmentioning
confidence: 96%
“…Many studies have shown that well-selected elderly patients benefit from transplant when compared with those remaining on dialysis, and that patient and graft survival rates are comparable to younger recipients. [1][2][3][4][5]16 Although there is a consensus on the benefit of kidney transplant in the elderly, the optimal immunosuppression strategy for these recipients is not been clearly elucidated. Reduced immune response and a potential for increased risk of infections and malignancies are the main concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Induction with r-ATG could be beneficial in these patients based on previous reports. 15,19 In our analysis, 53% of all ECD kidney recipients underwent r-ATG induction, with 73% on chronic steroid maintenance. The results of our study suggest that one has to be cautious in using chronic steroid maintenance in r-ATG-induced ECD kidney recipients especially those over 60 years of age.…”
Section: Sabiha M Hussain Et Al/experimental and Clinical Transplantmentioning
confidence: 92%
“…15 With preferential allocation of organs, elderly recipients are more likely to receive ECD kidneys. Based on Scientific Registry of Transplant Recipients data analysis, Schold and associates proposed a model toward efficient use of resources in which older patients can substantially reduce their wait time with receipt of ECD kidneys.…”
Section: Sabiha M Hussain Et Al/experimental and Clinical Transplantmentioning
confidence: 99%
See 1 more Smart Citation